علوم اسلامیہ کی تدوین میں برصغیر کی خواتین کا کردار: Contributions of the Women’s of the Subcontinent in Compilation of Islamic Studies (Al-Qamar, 2021)
The compilation of Islamic studies includes the services of women of the subcontinent as well as women of the world, including Zeb-un-Nisa, daughter of Mughal King Aurangzeb Alamgir, and Mahmood-un-Nisa Begum of Hyderabad Deccan. He wrote a simple translation and commentary of the Holy Quran in two volumes which has its own distinct identity. Nawab Sikandar Jahan Begum, the ruler of Bhopal, had Sheikh Ahmad Daghestani translate the Quran into Turkish. His daughter and successor Nawab Shah Jahan Begum provided full financial support to Muhammadan Anglo Oriental College Aligarh. He had Maulana Jamaluddin, the Minister of State for Bhopal, translate the Holy Quran into Pashto. He authored a book, Madarij-ul-Quran, which was published in 1935 from Bhopal. This commentary of Surah Yusuf by Rani Gul Badan Begum has been written in Urdu with Arabic text and translation. This commentary was initially published in Oriental College Magazine, Punjab University, Lahore. It was later published in a book form from Lahore in 1933. Begum Noor Mahal belonged to the Hatim Khan dynasty of a Bengali family. Nadeem Sehar Umbereen wrote a dissertation on Women and Services of the Qur'an and received her PhD from Jamia Millia Islamia, New Delhi. Written by Dr. Najma Sultana Sahiba in her book “The Importance of Education in Islam and the Role of Women”, the book focuses on 9 topics. The role of women in Ghazwaat Nabavi, women's scholarly achievements, the concept of women's education in Islam, the importance of girls' education in Islam, women's scholarly literary social services, some important sources and references "and many other important topics. ۔ At the same time, for her PhD degree from Maulana Azad National Urdu University, India, she wrote her dissertation entitled "The Educational Position of Muslim Women". Syed Sardar Begum's name is Akhtar. Allama Iqbal had a profound effect on her speech. She was a poetess. Nearly all genres of ghazals, qasids, mukhmas, mutman, masdas, rubai, quatas, masnavi and manaqib are found. There are 184 ghazals in her divan. Due to his keen interest in reading, his library was full of books on science and art and he was also interested in music. He has also written essays on Sufism, ethics and advice in poetry.
Keywords: Contributions; Women; Subcontinent Islamic Studies